Ups and downs: How economic growth affects policy interactions - Florens Flues; Andreas Löschel; Benjamin Johannes Lutz; Oliver Schenker (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Current climate and energy policy has to operate under an ex-ante unforeseen economic crisis. An obvious consequence is the collapse of prices for carbon emission allowances as, for example, seen in the European Union. However, this price collapse may be amplified by the interaction of a carbon emission cap and supplementary policy targets such as the minimum shares for renewables in the power sector. The static interaction between climate and renewable policies has been discussed extensively. This paper extends this debate by analysing how uncertain differences in medium to long-run growth rates affect the effciency and effectiveness of a policy portfolio containing an emission trading scheme and a target for a minimum renewable share. Making use of a simple partial equilibrium model we identify an asymmetric interaction of emissions trading and renewable quotas with respect to different growth rates of an economy. The results imply that unintended consequences of the policy interaction may be particularly severe and costly when economic growth is low and that carbon prices are more sensitive to changes in economic growth if they are applied in combination with renewable energy targets. Our main example for the policy interaction is the EU, yet our research also relates particularly well to the uncertainty of economic growth in fast growing emerging economies like China.
urn:nbn:de:bsz:180-madoc-346942
Keywords: Q43; Q48; Q58; 330; EU Climate Policy; Growth Uncertainty; Overlapping Regulation